THE ROLE OF BRAND AWARENESS AS A MEDIATOR OF THE EFFECT OF CONTENT MARKETING AND INFLUENCER MARKETING ON PURCHASE DECISION AT MILLY JADE - Michelle Letitia` Valmai; Metta Padmalia (International Journal of Economics, Business and Accounting Research (IJEBAR), 2026)
This study aims to examine the role of brand awareness in mediating the relationship between content marketing and influencer marketing on purchase decisions at Milly Jade. The research variables consist of independent variables, namely content marketing and influencer marketing; the dependent variable, namely purchase decision; and the mediating variable, namely brand awareness. This study employs a quantitative research method, with data processing conducted using Structural Equation Modeling (SEM) - Partial Least Square (PLS). The sampling technique used is purposive sampling, with a questionnaire instrument utilizing a Likert scale. The population of this study consists of Milly Jade's online shop customers. The sample for this study includes 210 respondents who purchased Milly Jade products. The results of the study indicate that content marketing affects purchase decision, influencer marketing affects purchase decision, and brand awareness partially mediates the effect of content marketing and influencer marketing on purchase decision.